2007
DOI: 10.1111/j.1582-4934.2007.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between cardiac oxidative stress and myocardial pathology due to acute and chronic norepinephrine administration in rats

Abstract: Background: To investigate the cardiotoxic role of reactive oxygen species (ROS) and of products derived from catecholamines auto-oxidation, we studied: (1) the response of antioxidant cardiac cellular defence systems to oxidative stress induced by norepinephrine (NE) administration, (2) the effect of NE administration on cardiac β1-adrenergic receptors by means of receptor binding assay, (3) the cellular morphological alterations related to the biologically cross-talk between the NE administration and cytokin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(97 citation statements)
references
References 49 publications
(61 reference statements)
3
93
0
1
Order By: Relevance
“…1,34 Meszaros et al 35 showed that administration of supramaximal dosages of ISO increased enddiastolic volume and end-diastolic pressure, contributing to ventricular dysfunctions, which possibly resulted from the auto-oxidation of catecholamines that stimulated oxidative stress via reactive mediators, leading to cardiotoxicity. 36 More interestingly, the ventricular dysfunction, as mentioned above, could be significantly prevented by antioxidants. 35,37 An increasing body of evidence suggests that free radicals, including reactive oxygen species and reactive nitrogen species, have long been recognized to act as the major mediators of cardiac injury, and antioxidants and free radical scavengers have been shown to minimize cardiac injury, which, to some extent, verifies that oxygen radicals have a key role in cardiac injury.…”
Section: Discussionmentioning
confidence: 77%
“…1,34 Meszaros et al 35 showed that administration of supramaximal dosages of ISO increased enddiastolic volume and end-diastolic pressure, contributing to ventricular dysfunctions, which possibly resulted from the auto-oxidation of catecholamines that stimulated oxidative stress via reactive mediators, leading to cardiotoxicity. 36 More interestingly, the ventricular dysfunction, as mentioned above, could be significantly prevented by antioxidants. 35,37 An increasing body of evidence suggests that free radicals, including reactive oxygen species and reactive nitrogen species, have long been recognized to act as the major mediators of cardiac injury, and antioxidants and free radical scavengers have been shown to minimize cardiac injury, which, to some extent, verifies that oxygen radicals have a key role in cardiac injury.…”
Section: Discussionmentioning
confidence: 77%
“…The mechanism underlying this phenomena is unclear but a number of potential contributing mechanisms have been proposed including mitochondrial oxidative stress, microvascular thrombi and increased sarcolemma membrane permeability 36,37 . Catecholamines have been shown to increase myocardial oxidative stress in experimental models, 38 and in a murine model of sepsis Haileselassie et al demonstrated that increased oxidative stress was a central factor in development of septic induced myocardial dysfunction. The observed increase in troponin is a concerning find as it suggests the increased vasopressor requirement is not a benign epiphenomena and may produce secondary cardiac injury.…”
Section: Discussionmentioning
confidence: 99%
“…However, GPx requires GSH to perform this function. GSH has a direct antioxidant function by reacting with superoxide radicals to produce GSSG (Neri et al, 2007;Franco & Cidlowski, 2009). In addition, the level of MDA reflects the extent of cell injury by oxidative stress.…”
Section: Discussionmentioning
confidence: 99%